Economic partnership agreements : a 'historic step' towards a 'partnership of equals'? - Meyn, Mareike (Overseas Development Institute LondonGB, 2008)
Argues that the (interim) EPAs initialled between the EU and less than half of all ACP states at the end of 2007 do not represent a 'historic step' in EU-ACP relations. Argues further that the enforcement of the EPA implementation is unlikely in some cases given the decreasing attractiveness of the EU market, and the Commission's dwindling capacity to sanction non-compliance by withdrawing preferences.